Social wireless sensor network toward device-to-device interactive Internet of Things services - Sunme Kim; Yongbin Yim; Seungmin Oh; Sang-Ha Kim (International Journal of Distributed Sensor Networks)
As wireless sensor networks have been typically designed for monitoring of environments or habitats, all sensed data flow down toward fixed sinks. With the proliferation of Internet of Things, a variety of services require that data should be delivered not to the fixed sinks but directly to operator-specified devices, such as actuators and inside sensor fields. Then, the data will directly trigger interactive and immediate actions at the devices for the services. We call this kind of service as a device-to-device interactive Internet of Things service. However, the wireless sensor networks with fixed architecture could not support the device-to-device interactive services. The services might have the sociality based on the service-specific organic relationships between sensor and device, or between devices according to the purpose of the service. Social wireless sensor network is the architecture and mechanism to define the organic relationships of sensing data and the flow of data per service dynamically and flexibly over wireless sensor networks. In this article, we propose the social wireless sensor network architecture, functions, and challenges to provide the sociality of the services over wireless sensor networks.